PERKEMBANGAN BAHASA ANAK 0- 3 TAHUN DALAM KELUARGA - I Gede Neil Prajamukti Wardhana (Program Magister Linguistik Universitas Udayana, 2013)
The aimed of this study was to determine the use of Indonesian children aged 0-3 years, namely Agus terms of phonological development and the effect of the use of Indonesian in vocabulary or pronunciation of simple sentences. This study used observation and interviews to his family and also see the use of language Agus already started to say the word or stringing sentences, although still less true , and see the interaction between the child with his family. The results of this study indicate the pronunciation of the language spoken by Agus at the age of 0-3 years which he can begin to utter the word ma .. ma .. - [ ma ] [ ma ], pa .. pa .. - [ pa ] [ pa ] and bu .. bu .. - [ bu ] [ bu ] and pronunciation of words is reversed as Eskali - [ ?skali ] = sekali, Pahaya - [ pahaya ] = Papaya , Kehalik - [ k?halik ] = kebalik , Eskalang - [ ?skala? ] = sekarang, Kehini - [ k?hini ] = kesini/disini, Hana - [ hana ] = panas. Child language development is influenced by environmental factors, especially families who apply Agus motherese, recasting, echoing, expanding.